Social legitimacy and religious-social validation: A study of mass marriage practices in South Bangka - Muhammad Safwan Jamil; Muhammad Okta Ridha Maulidian; Hifjir (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
Kawin herdek is a mass wedding tradition that is also included in the WBTb cultural heritage category. This study aims to analyze social legitimacy, the interaction of three legal systems, and the multidimensional application of the kawin herdek mass wedding tradition for the participants and the community. The study used a qualitative descriptive method and was explained using the Miles and Huberman model. The results show that kawin herdek has strong social legitimacy because it is positioned as a means of strengthening communal solidarity and reducing wedding costs. From a customary law perspective, it is considered valid because it fulfills local customs, traditional symbols, and is recognized by traditional and community leaders. Meanwhile, from a religious law perspective, it is acceptable because it fulfills the requirements of the pillars of marriage, although some religious leaders urge the need for proper registration. From a state law perspective, this practice often encounters legal obstacles because not all marriages are immediately registered at the Office of Religious Affairs (KUA). This study has a social impact by showing that kawin herdek can strengthen social cohesion and expand kinship networks. Religious implications are evident in the community’s efforts to align customary requirements with religious obligations.